Melatonin Inhibits the Progression of Oral Squamous Cell Carcinoma via Inducing miR-25-5p Expression by Directly Targeting NEDD9 - Wang, Yanling; Tao, Bo; Li, Jiaying; Mao, Xiaoqun; He, Wei; Chen, Qinbiao (Frontiers in Oncology, 2020)
Melatonin exerts anti-cancer roles in various types of cancers. However, to the best of our knowledge, its role in oral squamous cell carcinoma (OSCC) is unknown. The present study aimed to investigate the role of melatonin and its underlying mechanism in OSCC. MTT, colony formation, wound healing, and transwell invasion assays proved that melatonin played anti-tumor effects in OSCC cells by inhibiting cell viability, proliferation, migration, and invasion in a concentration-dependent manner. The RT-qPCR analysis showed that miR-25-5p was significantly upregulated after melatonin treatment. Further, miR-25-5p might be involved in melatonin-induced inhibitory effects on the biological behavior of OSCC. The expression of miR-25-5p was decreased in tumor tissues and OSCC cells detected by RT-qPCR. MTT assay, colony formation assay, and TUNEL staining indicated miR-25-5p overexpression inhibited OSCC cell viability, proliferation, and induced OSCC cell apoptosis. Furthermore, wound healing, transwell invasion assay, and animal experiments suggested that miR-25-5p might exert suppressive effects on the migration, invasion, and tumor formation of OSCC cells, while miR-25-5p knockdown exhibited the opposite effects in OSCC cells. Bioinformatics analysis, western blot analysis, and luciferase reporter assay suggested that neural precursor cell expressed developmentally downregulated protein 9 (NEDD9) was proved to be a putative target for miR-25-5p. The role of NEDD9 in inhibiting OSCC cell proliferation, invasion, and migration was verified with NEDD9 siRNA transfection. Thus, melatonin exerted anti-proliferative, anti-invasive, and anti-migrative effects on OSCC via miR-25-5p/NEDD9 pathway. Melatonin could be applied as a potential novel drug on treating OSCC.